A diffused air-permeable refractory brick and its production process
By using silicon/titanium coated corundum particles and other micropowder materials in the breathable refractory bricks, combined with phenolic resin and oxide powder, to form magnesium-aluminum spinel and non-oxide reinforced phases, the problems of poor mechanical toughness and poor thermal shock resistance of the breathable refractory bricks are solved, and the material's slag corrosion resistance and thermal shock resistance are significantly improved.
Patent Information
- Application Number
- CN202510000225.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-02
AI Technical Summary
Existing breathable refractory bricks have problems with poor mechanical toughness and poor thermal shock resistance.
Silicon/titanium coated corundum particles, alumina powder, magnesium oxide powder and other raw materials are used to form magnesium aluminum spinel and non-oxide fiber-like reinforced phases through phenolic resin as a binding agent, thereby improving the slag corrosion resistance and thermal shock resistance of refractory bricks.
It improves the slag corrosion resistance, thermal shock resistance and mechanical properties of diffuse breathable refractory bricks, and enhances the denseness of the material and the interface bonding strength.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a diffused air-permeable refractory brick and a production process thereof. Background Art
[0002] The ladle bottom argon blowing process is a widely used method of molten steel refining in steel production, and the breathable refractory brick is one of the important functional components for realizing argon blowing treatment of molten steel. It plays a vital role in homogenizing the temperature of molten steel and removing inclusions, and is the key to improving the quality of high-quality steel.
[0003] At present, the types of breathable refractory bricks are mainly divided into diffused breathable refractory bricks, straight-through breathable refractory bricks, slit breathable refractory bricks, etc. Straight-through breathable bricks have the advantages of stable ventilation airflow, high strength, and long service life, but the channels are prone to blockage in the later period of use. Slit breathable refractory bricks have the advantages of good air permeability and poor penetration of molten steel; but there is a problem that the airflow is difficult to control under low gas flow, and it needs to be frequently blown and ablated. Dispersed breathable refractory bricks have the advantages of high blowing rate, less oxygen burning times, and long service life.
[0004] At present, the dispersed breathable refractory bricks mainly adopt the corundum-spinel system. Magnesium-aluminum spinel has the characteristics of high melting point, stable chemical properties, and good corrosion resistance. Introducing it into the corundum matrix as the second phase can optimize the thermal shock resistance of the material.
[0005] The Chinese patent application document with publication number CN102617171A discloses a MgAlON-bonded aluminum-magnesium breathable brick and its preparation method, wherein the breathable brick is made of sintered corundum particles, alumina fine powder, metal aluminum powder and fused magnesia fine powder as raw materials, and phenolic resin is added, mixed and rolled, machine pressed and formed, and heated and calcined to obtain the MgAlON-bonded aluminum-magnesium breathable brick. However, the impurity phases B2O3, CaO, etc. in the magnesia raw material may react with other components to form a low melting point phase, reduce the strength and toughness of the refractory brick, and thus affect the mechanical properties. Summary of the invention
[0006] Existing air-permeable refractory bricks have the problems of poor mechanical toughness and poor thermal shock resistance. In order to solve this problem, the present invention provides a diffuse air-permeable refractory brick and a production process thereof.
[0007] In order to achieve the purpose of the present invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a diffused air-permeable refractory brick, which is made of the following raw materials in parts by weight:
[0009] 50-60 parts of silicon / titanium coated corundum particles, 30-40 parts of corundum particles, 15-20 parts of alumina powder, 8-12 parts of magnesium oxide powder, 3-5 parts of activated alumina powder, 1-3 parts of niobium pentoxide, 4-8 parts of phenolic resin, and 3-5 parts of water.
[0010] Preferably, the aluminum oxide micropowder has an aluminum oxide content of ≥99% and a particle size of ≤5 μm; the magnesium oxide micropowder has an aluminum oxide content of ≥99% and a particle size of ≤10 μm; and the activated aluminum oxide micropowder has an aluminum oxide content of ≥99% and a particle size of ≤2 μm.
[0011] By adopting the above technical solution, magnesium oxide powder with this particle size is more likely to react with aluminum oxide powder to form magnesium aluminum spinel, and thus has more time for sintering reaction; the active aluminum oxide powder with this particle size fills the pores in the refractory bricks, making the refractory bricks denser.
[0012] Preferably, the method for preparing the silicon / titanium coated corundum particles comprises the following steps:
[0013] Silicon powder, titanium powder, corundum particles and a binder are uniformly mixed, dried, and calcined at 1400-1500° C. in a nitrogen atmosphere to obtain silicon / titanium-coated corundum particles.
[0014] Preferably, the mass ratio of the silicon powder, titanium powder and corundum particles is (12-18):(6-10):100.
[0015] By adopting the above technical solution, under this ratio, silicon powder and titanium powder can be tightly coated on the surface of the corundum particles to form a uniform coating layer.
[0016] Preferably, the amount of the binder used accounts for 2%-4% of the total mass of the silicon powder, titanium powder and corundum particles.
[0017] Preferably, the binder is composed of phenolic resin, silica sol and isopropyl alcohol in a mass ratio of (8-11):(1-4):10.
[0018] By adopting the above technical solution, under this ratio, the binder can effectively connect the silicon powder, titanium powder and corundum particles together, thereby improving the strength and stability of the refractory bricks.
[0019] Preferably, the corundum particles are composed of corundum particles with particle sizes of 1-2 mm, 0.1-1 mm, and 0.02-0.1 mm, respectively, in a mass ratio of (2-4):(1.6-2.2):1.
[0020] Preferably, the silicon / titanium coated corundum particles are composed of silicon / titanium coated corundum particles with particle sizes of 1-2 mm, 0.1-1 mm, and 0.02-0.1 mm, respectively, in a mass ratio of (3-5):(1-2):1.
[0021] By adopting the above technical scheme, the particle grading of all corundum particles is adjusted, the size of pores is reduced and the strength of materials is improved while ensuring air permeability; 1-2mm particles play a skeleton role in breathable refractory bricks, supporting the entire structure and improving the compressive strength and flexural strength of breathable bricks; 0.1-1mm particles are filled in the gaps between 1-2mm particles, enhancing the structural stability of the material; 0.02-0.1mm particles are filled in smaller gaps to make the structure tighter, reduce the size of pores while ensuring air permeability, and improve the thermal shock resistance of refractory bricks.
[0022] Preferably, the corundum particles are composed of dense fused corundum particles and sintered plate-shaped corundum particles in a mass ratio of 1:(1-3).
[0023] By adopting the above technical scheme, dense fused corundum has higher strength and hardness, while sintered plate-shaped corundum has better thermal shock resistance. Under this ratio, the thermal shock resistance and mechanical strength of the breathable refractory bricks reach the optimum.
[0024] In a second aspect, the present invention provides a production process for the above-mentioned diffused air-permeable refractory bricks, comprising the following steps:
[0025] S1: mixing alumina micropowder, magnesium oxide micropowder, activated alumina micropowder and niobium pentoxide uniformly to obtain a premix;
[0026] S2: mixing the silicon / titanium coated corundum particles after ball milling and screening with the corundum particles, adding the premix, binder and water and mixing them evenly to obtain a mixture, vibrating the mixture and casting it, curing it at room temperature for 24 hours, then demolding it, and drying it to obtain a green body;
[0027] S3: placing the green body in a high temperature furnace and calcining it in a nitrogen atmosphere to obtain a diffused and permeable refractory brick.
[0028] Preferably, in S3, the calcination process is: heating to 1000-1100°C at a rate of 8°C / min, and keeping warm for 1-3h; heating to 1450-1500°C at a rate of 5°C / min, and keeping warm for 3-8h.
[0029] By adopting the above technical solution, ball milling can eliminate the irregular sharp angles between silicon / titanium coated corundum particles and corundum particles, and the nearly spherical particles can increase the uniformity and fluidity of the mixture.
[0030] In summary, the beneficial effects of the present invention are:
[0031] (1) The present invention uses corundum particles as the main raw material, and replaces part of the corundum particles with silicon / titanium coated corundum particles, and introduces alumina micropowder, magnesium oxide micropowder and other substances, and uses phenolic resin as a binder. The corundum aggregate can generate a stable and high-temperature resistant magnesium-aluminum spinel phase in situ with the magnesium oxide micropowder. The prepared diffused permeable refractory brick has the advantages of strong slag erosion resistance, good thermal shock resistance, strong mechanical properties, etc.
[0032] (2) The silicon / titanium coated corundum particles prepared by the present invention can react with nitrogen to generate non-oxide fibrous reinforcement phases such as TiN and Si3N4, which have the advantages of high strength and low thermal expansion coefficient. When coated on the surface of the corundum particles, they can bridge the corundum aggregate and the matrix, enhance the interface bonding strength, and improve the thermal shock resistance and toughness of the refractory bricks. At the same time, the generated TiN, Si3N4 and other substances have low wettability with molten steel, which can improve the slag erosion resistance of the refractory bricks.
[0033] (3) The present invention introduces a small amount of silica sol into the binder to form a stable three-dimensional silicon-oxygen network structure, thereby improving the chemical stability of the refractory bricks; the nano-silicon dioxide particles can also fully contact with the alumina powder to form a mullite network structure, thereby improving the thermal shock resistance of the refractory bricks; at the same time, a small part of the agglomeration of the nano-silicon dioxide particles can change the direction of crack propagation and slow down the propagation of cracks caused by thermal shock;
[0034] (4) The present invention introduces niobium pentoxide into the refractory bricks, so that it is dispersed in the refractory bricks to form an effective reinforcement phase, thereby improving the toughness of the refractory bricks and further improving the thermal shock resistance of the material. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is explained in detail below with reference to several representative embodiments of the present invention.
[0036] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified.
[0037] Description of the raw materials used in the examples and comparative examples of the present invention:
[0038] The alumina content in dense fused corundum particles and sintered plate-shaped corundum particles is ≥99%;
[0039] The alumina content in alumina micropowder is ≥99% and the particle size is ≤5μm;
[0040] Magnesium oxide powder content ≥99%, particle size ≤10μm;
[0041] The alumina content in the activated alumina micropowder is ≥99% and the particle size is ≤2μm;
[0042] Niobium pentoxide has a niobium pentoxide content of ≥99% and a particle size of ≤10μm;
[0043] Phenolic resin is a thermosetting phenolic resin with a solid content of 75%-80%;
[0044] Silica sol, solid content ≥50%.
[0045] Example 1
[0046] A diffused air-permeable refractory brick in this embodiment is made from the raw materials in Table 1;
[0047] The corundum particles in this embodiment are composed of dense fused corundum particles and sintered plate-shaped corundum particles in a mass ratio of 1:2.
[0048] The specific steps of the method for preparing silicon / titanium coated corundum particles in this embodiment are as follows:
[0049] 16 g of silicon powder, 6 g of titanium powder, 100 g of corundum particles and 3.66 g of binder were added into a mixer and stirred for 20 min, dried at 80 ° C for 6 h, transferred into a high-temperature calcining furnace and heated to 1450 ° C at a rate of 5 ° C / min under a nitrogen atmosphere, kept at this temperature for 5 h, and naturally cooled to room temperature to obtain silicon / titanium coated corundum particles;
[0050] The binder of this embodiment is composed of phenolic resin, silica sol and isopropyl alcohol in a mass ratio of 8:3:10.
[0051] The production process of a diffused air-permeable refractory brick in this embodiment comprises the following specific steps:
[0052] S1: Alumina micropowder, magnesium oxide micropowder, activated alumina micropowder and niobium pentoxide are stirred in a mixer for 30 minutes to obtain a premix;
[0053] S2: The silicon / titanium coated corundum particles after ball milling and sieving are mixed evenly with the corundum particles, and the premix, binder and water are added to the mixture and stirred in a mixer for 2 hours to obtain a mixture, and the mixture is molded by vibration casting, and the mixture is demolded after curing at room temperature for 24 hours, and the demolded sample is dried at 110°C for 24 hours to obtain a green body;
[0054] S3: Place the blank in a high temperature furnace and heat it to 1100°C at a rate of 8°C / min under a nitrogen atmosphere, and keep it warm for 2 hours; heat it to 1500°C at a rate of 5°C / min, and keep it warm for 8 hours. After cooling to room temperature, a diffused breathable refractory brick is obtained.
[0055] Example 2
[0056] A diffused air-permeable refractory brick in this embodiment is made from the raw materials in Table 1;
[0057] The corundum particles in this embodiment are composed of dense fused corundum particles and sintered plate-shaped corundum particles in a mass ratio of 1:1.
[0058] The specific steps of the method for preparing silicon / titanium coated corundum particles in this embodiment are as follows:
[0059] 12 g of silicon powder, 8 g of titanium powder, 100 g of corundum particles and 4.8 g of binder were added into a mixer and stirred for 20 min, dried at 80 °C for 6 h, transferred into a high-temperature calcining furnace and heated to 1500 °C at a rate of 5 °C / min under a nitrogen atmosphere, kept at this temperature for 5 h, and naturally cooled to room temperature to obtain silicon / titanium coated corundum particles;
[0060] The binder of this embodiment is composed of phenolic resin, silica sol and isopropyl alcohol in a mass ratio of 8:4:10.
[0061] The production process of a diffused air-permeable refractory brick in this embodiment comprises the following specific steps:
[0062] S1: Alumina micropowder, magnesium oxide micropowder, activated alumina micropowder and niobium pentoxide are stirred in a mixer for 30 minutes to obtain a premix;
[0063] S2: The silicon / titanium coated corundum particles after ball milling and sieving are mixed evenly with the corundum particles, and the premix, binder and water are added to the mixture and stirred in a mixer for 2 hours to obtain a mixture, and the mixture is molded by vibration casting, and the mixture is demolded after curing at room temperature for 24 hours, and the demolded sample is dried at 110°C for 24 hours to obtain a green body;
[0064] S3: Place the blank in a high temperature furnace and heat it to 1000°C at a rate of 8°C / min under a nitrogen atmosphere, and keep it warm for 1 hour; heat it to 1450°C at a rate of 5°C / min, and keep it warm for 5 hours. After cooling to room temperature, a diffused breathable refractory brick is obtained.
[0065] Example 3
[0066] A diffused air-permeable refractory brick in this embodiment is made from the raw materials in Table 1;
[0067] The corundum particles in this embodiment are composed of dense fused corundum particles and sintered plate-shaped corundum particles in a mass ratio of 1:3.
[0068] The specific steps of the method for preparing silicon / titanium coated corundum particles in this embodiment are as follows:
[0069] 18 g of silicon powder, 8 g of titanium powder, 100 g of corundum particles and 2.52 g of binder were added into a mixer and stirred for 20 min, dried at 80 °C for 6 h, transferred into a high-temperature calcining furnace and heated to 1400 °C at a rate of 5 °C / min under a nitrogen atmosphere, kept at this temperature for 5 h, and naturally cooled to room temperature to obtain silicon / titanium coated corundum particles;
[0070] The binder of this embodiment is composed of phenolic resin, silica sol and isopropyl alcohol in a mass ratio of 11:2:10.
[0071] The production process of a diffused air-permeable refractory brick in this embodiment comprises the following specific steps:
[0072] S1: Alumina micropowder, magnesium oxide micropowder, activated alumina micropowder and niobium pentoxide are stirred in a mixer for 30 minutes to obtain a premix;
[0073] S2: The silicon / titanium coated corundum particles after ball milling and sieving are mixed evenly with the corundum particles, and the premix, binder and water are added to the mixture and stirred in a mixer for 2 hours to obtain a mixture, and the mixture is molded by vibration casting, and the mixture is demolded after curing at room temperature for 24 hours, and the demolded sample is dried at 110°C for 24 hours to obtain a green body;
[0074] S3: Place the blank in a high temperature furnace and heat it to 1050°C at a rate of 8°C / min under a nitrogen atmosphere, and keep it warm for 3 hours; heat it to 1450°C at a rate of 5°C / min, and keep it warm for 3 hours. After cooling to room temperature, a diffused breathable refractory brick is obtained.
[0075] Example 4
[0076] A diffused air-permeable refractory brick in this embodiment is made from the raw materials in Table 1;
[0077] The corundum particles in this embodiment are composed of dense fused corundum particles and sintered plate-shaped corundum particles in a mass ratio of 1:2.
[0078] The specific steps of the method for preparing silicon / titanium coated corundum particles in this embodiment are as follows:
[0079] 18 g of silicon powder, 10 g of titanium powder, 100 g of corundum particles and 5.12 g of binder were added into a mixer and stirred for 20 min, dried at 80 °C for 6 h, transferred into a high-temperature calcining furnace and heated to 1500 °C at a rate of 5 °C / min under a nitrogen atmosphere, kept at this temperature for 5 h, and naturally cooled to room temperature to obtain silicon / titanium coated corundum particles;
[0080] The binder of this embodiment is composed of phenolic resin, silica sol and isopropyl alcohol in a mass ratio of 10:1:10.
[0081] The production process of a diffused air-permeable refractory brick in this embodiment comprises the following specific steps:
[0082] S1: Alumina micropowder, magnesium oxide micropowder, activated alumina micropowder and niobium pentoxide are stirred in a mixer for 30 minutes to obtain a premix;
[0083] S2: The silicon / titanium coated corundum particles after ball milling and sieving are mixed evenly with the corundum particles, and the premix, binder and water are added to the mixture and stirred in a mixer for 2 hours to obtain a mixture, and the mixture is molded by vibration casting, and the mixture is demolded after curing at room temperature for 24 hours, and the demolded sample is dried at 110°C for 24 hours to obtain a green body;
[0084] S3: Place the blank in a high temperature furnace and heat it to 1000°C at a rate of 8°C / min under a nitrogen atmosphere, and keep it warm for 1 hour; heat it to 1500°C at a rate of 5°C / min, and keep it warm for 5 hours. After cooling to room temperature, a diffused breathable refractory brick is obtained.
[0085] Table 1 Raw material ratio
[0086]
[0087] Comparative Example 1
[0088] The difference from Example 1 is that in this comparative example, the silicon / titanium coated corundum particles are replaced by an equal amount of corundum particles, and the rest is the same as Example 1.
[0089] Comparative Example 2
[0090] The difference from Example 1 is that niobium pentoxide is not added in this comparative example, and the rest is the same as Example 1.
[0091] Comparative Example 3
[0092] The difference from Example 1 is that in this comparative example, an equal amount of zirconium oxide is used to replace niobium pentoxide, and the rest is the same as Example 1.
[0093] Comparative Example 4
[0094] The difference from Example 1 is that in this comparative example, no silica sol is added in the preparation of silicon / titanium coated corundum particles, and the rest is the same as Example 1.
[0095] Comparative Example 5
[0096] The difference from Example 1 is that in the preparation of silicon / titanium coated corundum particles in this comparative example, the added amounts of silicon powder and titanium powder are 32 g and 15 g respectively, and the rest are the same as Example 1.
[0097] Comparative Example 6
[0098] The difference from Example 1 is that in the preparation of silicon / titanium coated corundum particles in this comparative example, the added amounts of silicon powder and titanium powder are 5 g and 3 g respectively, and the rest are the same as Example 1.
[0099] Comparative Example 7
[0100] The difference from Example 1 is that the silicon / titanium coated corundum particles in this comparative example are composed of corundum particles with particle sizes of 1-2 mm, 0.1-1 mm, and 0.02-0.1 mm in a mass ratio of 10:1:1, and the rest are the same as Example 1.
[0101] Comparative Example 8
[0102] The difference from Example 1 is that the corundum particles in this comparative example are composed of corundum particles with particle sizes of 1-2 mm, 0.1-1 mm, and 0.02-0.1 mm in a mass ratio of 7:10:1, and the rest are the same as Example 1.
[0103] Related tests
[0104] The diffused air-permeable refractory bricks prepared in Examples 1 to 4 and Comparative Examples 1 to 7 were subjected to relevant performance tests, and the test results are shown in Table 2.
[0105] Table 2 Test results
[0106]
[0107] From the comparison between Example 1 and Comparative Example 1, it can be seen that the addition of silicon / titanium coated corundum particles can improve the high-temperature flexural strength and thermal shock resistance of the refractory bricks, and significantly improve the slag erosion resistance of the refractory bricks.
[0108] By comparing Example 1 with Comparative Examples 2 and 3, it can be seen that the addition of niobium pentoxide can play a role in dispersion toughening; if it is replaced with an equal amount of zirconium oxide, the cracks generated by the phase change of zirconium oxide may be combined with the cracks generated in situ in the magnesia-aluminum spinel and the microcracks generated after the binder is sintered, and they may be intertwined and extended with each other, and the originally tightly packed particle structure may be destroyed, thereby reducing the density, flexural resistance and other properties of the refractory bricks.
[0109] It can be seen from Example 1 and Comparative Example 4 that the addition of silica sol can alleviate the further expansion of cracks, increase the density of refractory bricks and thus improve the high-temperature flexural strength of refractory bricks.
[0110] By comparing Example 1 with Comparative Examples 5 and 6, it can be seen that the addition of silicon powder and titanium powder can generate substances such as silicon nitride, which do not wet with steel slag, reduce the chance of steel slag corroding refractory bricks, and improve the slag corrosion resistance of refractory bricks; in an oxygen atmosphere, it can also form a dense silicon dioxide film on the surface of the corundum particles, further improving the slag corrosion resistance and antioxidant properties of the refractory bricks; too much or too little silicon powder and titanium powder added will affect the coating of silicon powder and titanium powder on the corundum particles, and reduce the relevant performance of the refractory bricks.
[0111] By comparing Example 1 with Comparative Examples 7 and 8, it can be seen that the particle size distribution of the silicon / titanium coated corundum particles and the corundum particles changes, and the relevant performance of the refractory bricks decreases, indicating that the particle size distribution of the silicon / titanium coated corundum particles and the corundum particles in the present invention has been optimized.
[0112] The above is an exemplary description of the present invention. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or equivalent replacement that can be done by other technicians in this field without expending creative labor falls within the protection scope of the present invention.
Claims
1. A diffused air-permeable refractory brick, characterized in that: The diffusion-permeable refractory brick is made of the following raw materials in parts by mass: 50-60 parts of silicon / titanium-coated corundum particles, 30-40 parts of corundum particles, 15-20 parts of alumina fine powder, 8-12 parts of magnesia fine powder, 3-5 parts of activated alumina fine powder, 1-3 parts of niobium pentoxide, 4-8 parts of phenolic resin, and 3-5 parts of water; The preparation method of the silicon / titanium-coated corundum particles comprises the following steps: Mix silicon powder, titanium powder, corundum particles and a binder evenly, dry, and calcine at 1400-1500°C in a nitrogen atmosphere to obtain silicon / titanium-coated corundum particles; In the preparation method of the silicon / titanium-coated corundum particles, the mass ratio of the amounts of silicon powder, titanium powder and corundum particles used is (12-18):(6-10):100; the binder is composed of phenolic resin, silica sol and isopropanol in a mass ratio of (8-11):(1-4):10; The particle size of the alumina fine powder is 5μm; the particle size of the activated alumina fine powder is ≤2μm; The corundum particles are composed of three kinds of corundum particles with particle sizes A, B, and C in a mass ratio of (2-4):(1.6-2.2):1; 1mm < A ≤ 2mm, 0.1mm < B ≤ 1mm, 0.02mm < C ≤ 0.1mm, and the silicon / titanium-coated corundum particles are composed of three kinds of silicon / titanium-coated corundum particles with particle sizes D, E, and F in a mass ratio of (3-5)∶(1-2)∶1; 1mm < D ≤ 2mm, 0.1mm < E ≤ 1mm, 0.02mm < F ≤ 0.1mm.
2. The diffused air-permeable refractory brick according to claim 1, characterized in that: In the preparation method of the silicon / titanium-coated corundum particles, the amount of the binder used accounts for 2%-4% of the total mass of the silicon powder, titanium powder and corundum particles.
3. The diffused air-permeable refractory brick according to claim 1, characterized in that: The corundum particles are composed of dense fused corundum particles and sintered tabular corundum particles in a mass ratio of 1∶(1-3).
4. A process for producing a diffused air-permeable refractory brick according to any one of claims 1 to 3, characterized in that: Comprises the following steps: S1: Mix alumina fine powder, magnesia fine powder, activated alumina fine powder and niobium pentoxide evenly to obtain a premix; S2: Mix the silicon / titanium-coated corundum particles and corundum particles after ball milling and sieving evenly, add the premix, binder and water and mix evenly to obtain a mixture, pour the mixture into a mold by vibration, cure at room temperature for 24h and then demold and dry to obtain a green body; S3: Place the green body in a high-temperature furnace and calcine in a nitrogen atmosphere to obtain the diffusion-permeable refractory brick.
5. The production process of a diffused air-permeable refractory brick according to claim 4, characterized in that: In the step S3, the calcination process is: heat up to 1000-1100°C at a rate of 8°C / min and hold for 1-3h; heat up to 1450-1500°C at a rate of 5°C / min and hold for 3-8h.
Citation Information
Patent Citations
MgAlON combined aluminum magenisum permeable brick and preparation method thereof
CN102617171A
Silicon nitride bonded corundum permeable brick and its preparation method
CN102276273A
Preparation method of erosion-resistant steel ladle air brick
CN117585993A